LESSON PLAN DEVELOPMENT ON THE TOPIC OF HOUSEHOLD ACCOUNTING TO ENHANCE SELF - ESTEEM IN JUNIOR HIGH SCHOOL STUDENTS IN SAMUTSAKHONBURANA SCHOOL - Suwanchasri, Pornkanok; Maharkan, Pattarapon; Sumbandit, Weena (Academic Journal of Thailand National Sports University, 2023)
The purposes of this research are 1) to develop the learning plan about household accounting for junior high students in according to promote self-esteem and 2) to evaluate learning which is in compliance with the learning plan about household accounting for junior high students in according to promote self-esteem. This research is an experimental research using a one - group pretest and posttest design from a purposive sampling sample group of 20 junior high students, in the first semester of the class of 2022 at Samutsakhonburana School. The experimental period is 20 hours along with research instruments which consist of a learning plan about household accounting, a capability test about household accounting, a student assessment of household accounting and a self - esteem assessment. The researcher uses statistics with frequencies percentage, mean, standard deviation and t - test (Pair Simple) Results 1) Learning Management Plan on Household Accounts, the Index of item Objective Congruence (IOC) is between 0.5 - 1. Household Accounting Proficiency Test the Index of item Objective Congruence (IOC) is between 0.75 - 1 Using Cronbach’s alpha correlation coefficient formula. The reliability analysis result was 0.896 Household Accounting Student Assessment from the Index of item Objective Congruence (IOC) is between 0.5 - 1 Self - esteem assessment from the Index of item Objective Congruence (IOC) is between 0.75 - 1 Using Cronbach’s alpha correlation coefficient formula. The reliability analysis result was 0.956 and 2) show that when comparing the pre - test and post - test of junior high students, school record about household accounting is statistically 0.5 statistical higher after study.